Financial Ratio Analysis to Assess Company Financial Performance at PT Perkebunan Sumatra Utara - Selvi Anita; Onan Marakali Siregar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Differential cost analysis is an analysis used to compare the differences between income and costs between existing alternatives to assist management in making decisions about which alternative to choose. Meanwhile, differential income is future information in the form of income that is different between decision alternatives and other decision alternatives. The aim of this research is to find out whether by-products can generate Differential Income at PT Pathemaang Raya Bitung. The research object is PT Pathemaang Raya Bitung. The research method used is Qualitative Descriptive. The research results show that by continuing the company's production of leftover goods into by-products, the company will generate Differential Income from the sale of these by-products.